2023
DOI: 10.1177/10901981231159679
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Food and Physical Activity Tracking Among Young Adults

Abstract: Background: Monitoring food intake and physical activity (PA) using tracking applications may support behavior change. However, few longitudinal studies identify the characteristics of young adults who track their behavior, findings that could be useful in designing tracking-related interventions. Our objective was to identify predictors of past-year food and PA tracking among young adults. Methods: Data were available for 676 young adults participating in the ongoing longitudinal Nicotine Dependence in Teens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Furthermore, fitness-and activity-tracking sensors consider factors like body size, weight, and stride length to estimate metrics such as calories burned or distance traveled. In these cases, there might be slight variations, based on sex differences, in body composition or average physical characteristics [68,78,79].…”
Section: Biomedical Sensors For Healthcare Monitoringmentioning
confidence: 99%
“…Furthermore, fitness-and activity-tracking sensors consider factors like body size, weight, and stride length to estimate metrics such as calories burned or distance traveled. In these cases, there might be slight variations, based on sex differences, in body composition or average physical characteristics [68,78,79].…”
Section: Biomedical Sensors For Healthcare Monitoringmentioning
confidence: 99%
“…In addition, participants had to quantify the number of hours of physical exercise performed during the week prior to the test. Both assessments were collected using the app "myfitnesspal ® " (V24.10.1) [17].…”
Section: Nutritional Assessment and Weekly Trainingmentioning
confidence: 99%
“…The semi-professional women's volleyball players performed a total of three days of training per week (90 min per training session) and played one match a week. An initial nutritional survey was carried out through the MyFitnessPal ® [44] application to determine the macronutrient intake (carbohydrates: 232.16 ± 45.62; fats: 74.33 ± 11.87; proteins: 92.15 ± 25.45; and total Kcal: 1966.34 ± 317.75). A priori sample size calculation was performed using a free online tool, G*Power (www.gpower.hhu.de; accessed on 2 February 2022), with a power level of 95% and an α _level of 0.05 and based on previous and similar studies [45], and it revealed that the sample size of >5 would be sufficient for the analysis.…”
Section: Participantsmentioning
confidence: 99%